Influence of substrate pasteurization, bag dimensions and organic supplement practices on yield and yield attributing parameters of Indian oyster mushroom, Pleurotus pulmonarius - latha, pagoti hema; Mohapatra, KB; Nayak, N.; Chinara, N. (Mushroom Research, 2022)
Pleurotus mushroom, generally referred to as â€˜Oyster mushroom or Dhingriâ€™ in India is relatively new to the mushroom industry. In India, Odisha is a leading state in terms of oyster mushroom production. The condition in most of agro-climatic situation in Odisha are suitable for growing oyster mushroom from month of July to February comprising of the rainy and winter season. Pleurotus pulmonarius is a potential protein source especially in developing countries, besides having minerals and vitamins. Besides its edibility it has also got pharmaceutical properties. Hence, Pleurotus pulmonarius could well be incorporated in to the mushroom farming system during winter season besides the ruling species, as this species was not in cultivation earlier. Four different substrate pasteurization methods along with untreated done (control) were evaluated for their yield potential and superiority of steam treatment of substrate in terms of realization of mushroom yield (98.90%) was established in the investigation. However, yield obtained (96.63%) out of the treatment pasteurized with chemical was statistically at par with the steam treatment, through it was associated with longer incubation period (17.50 d) and crop duration (24.25 d). The untreated substrate (control) produced the lowest yield (79.28%).Â Nine organic supplements including control were evaluated for their influence on yield and yield attributing parameters of Pleurotus pulmonarius. The biological efficiency was reported numerically highest (93.37%) in boiled wheat which was at par with the yields realized from chicken manure (93.07%), boiled maize (92.53%), rice bran (92.33%), untreated control (91.07%), maize meal (91.10%) and bengal gram powder (90.99%). Among the six diverse bag dimensions, 30 Ã— 25 cm bag accommodating 1500g substrate was superior in respect of biological efficiency. Â